Short-term effectiveness of baricitinib in children with refractory and/or severe juvenile dermatomyositis - Wang, Zhaoling; Zheng, Qi; Xuan, Wenjie; Xu, Xisheng; Lu, Meiping; Wu, Jianqiang; Zou, Lixia; Xu, Yiping; Xu, Xuefeng (Frontiers in Pediatrics, 2022)
Abstract Objective: To determine the short-term effectiveness and safety of baricitinib in children with refractory and/or severe juvenile dermatomyositis (rsJDM) in a real-world setting. Methods: This was a single-center retrospective study, that included 20 children with rsJDM. They were all treated using baricitinib combined with steroids and other immunosuppressive agents. The childhood myositis assessment scale (CMAS) and PRINTO remission criteria were used to evaluate the disease severity and treatment outcome at 0, 4, 12, and 24 weeks after initiation of baricitinib. Results: The skin rash improved in 95% of patients (19/20) at week 24, with a significant decrease of skin-DAS at weeks 12 (6.0 vs 2.0, p<0.05] and week 24 [6.0 vs 1.0, p<0.05) by median statistics. The CMAS score increased significantly at week 12 (41.0 [29.0, 44.0] vs 46.0 [42.0, 52.0], p<0.05) and week 24 (41.0 [29.0, 44.0] vs 50.0 [45.0, 52.0], p<0.05), as did the manual muscle testing (MMT)-8 score at week 24 (73.0 [610, 76.0] vs 79.0 [77.0, 80.0], p<0.05). At 24 weeks, complete response (CR) and partial response (PR) were achieved in 75% (15/20) and 15% (3/20) respectively. The dose of corticosteroids (CS) decreased by 37% from the baseline (0.53 [0.42, 1.00] mg/kg) to week 12 (0.33 [0.18, 0.40] mg/kg) (p<0.05), and by 49% at week 24 (p<0.05). No serious side effects were observed. Conclusion: Baricitinib combined with traditional immunosuppresants treatment was efficacious in rsJDM. Add-on therapy of baricitinib was helpful for tapering CS dose. No serious side effects were observed in this study.